Pengaruh Faktor Pengungkapan Corporate Social Responsibility - Soemaryono Soemaryono (Universitas Kristen Indonesia Toraja, 2024)
Research objective: To empirically test the influence of business risk, financial risk and operational risk on corporate social responsibility. The research object is gas, oil and coal sub-sector companies listed on the Indonesian stock exchange. The total sample was 17 companies for 5 years. Hypothesis testing uses the F test and t test. The results of the F test show that simultaneously business risk factors, financial risk factors and operational risk factors influence corporate social responsibility. Meanwhile, the results of the hypothesis using tests show that each factor of business risk, financial risk and operational risk has a partial effect on corporate social responsibility.